Professionalisation and its consequences for the governance of sports clubs in semi-professional team sports - Raphael Stieger; Romano Meier; Grazia Lang; Siegfried Nagel (Bern Open Publishing, 2023)
Sports clubs in semi-professional team sports professionalise their management particularly often due to expectations from internal and external stakeholders. Likely, they separate their elite section from other sections at some point during their professionalisation process. Promoting factors are the entrepreneurial risks and the high use of resources of the elite section. However, there are different approaches regarding the legal form of the separated elite section. While some sports clubs organise the elite section as a separated club, others choose a profit oriented legal form, like a limited liability company (LLC) or a stock company. Here, the following question arises: What are the consequences of the varying approaches for the governance of the sports clubs? Nagel et al. (2015) use a multi-level framework for the analysis of professionalisation in sports federations, which can be similarly used to analyse professionalisation processes in sports clubs. The framework shows, that professionalisation forms can lead to positive and negative consequences, such as changes in the governance structures. However, the chosen legal form and its (non) profit orientation leaves room for club-specific governance structures (Lang et al., 2019). This study is part of an international project on professionalisation processes of sports clubs. The research design is a case study design. It analyses two Swiss sports clubs that engage in a men's semi-professional team sports league. Both sport clubs separated their elite and amateur sections. The volleyball club organised the elite section as a member association, just like the amateur section. The handball club chose a LLC for their elite section. Data collection consisted of three parts: documentary analysis, expert interviews with decision-makers and focus groups with club members. The data was analysed using causation coding and visualisation strategies. The results show, that the elite section of the volleyball club employed a full-time paid CEO, while the management of the handball club's LLC relied exclusively on voluntary work. This might be explained by more financial resources of and higher demands on the international playing volleyball club. For both sports clubs, a decreasing identification of the amateur section with the elite section was a challenge at the beginning of the separation. Although both clubs believe that they have overcome this challenge thanks to joint events, the recruitment of volunteers for the elite sports is still a challenge. In conclusion, the professionalisation processes and the separation of elite and amateur sports led to changes in the governance of the sports clubs. However, the assumption that profit oriented legal forms tend to employ more paid staff could not be confirmed. Future research is needed to challenge these findings and to discover further approaches of governance structures. References Lang, G., Ströbel, T., & Nagel, S. (2019). Professionalization forms in mixed sport industries: is it time to rethink the stereotypes of non-profit and for-profit sport organizations? Managing Sport and Leisure, 24(4), 208-225. https://doi.org/10.1080/23750472.2019.1611470 Nagel, S., Schlesinger, T., Bayle, E., & Giauque, D. (2015). Professionalisation of sport federations: A multi-level framework for analysing forms, causes and consequences. European Sport Management Quarterly, 15(4), 407-433. https://doi.org/10.1080/16184742.2015.1062990